Adsorptive separation of emulsified oil in wastewater using biosorbents - Ibrahim, S.; Ang, Ha Ming; Wang, Shaobin (JOHN WILEY & SONS INC, 2012)
An agricultural waste, barley straw, was chemically modified using a cationic surfactant hexadecylpyridinium chloride monohydrate (CPC) to obtain a biosorbent for removal of emulsified mineral oil from aqueous solution. The physical and chemical properties of the raw and surfactant-modified barley straw (SMBS) were characterized by N2 adsorption, bulk density, Fourier transforms infrared spectra and the composition of cellulose, hemicellulose and lignin. The adsorption tests were performed using a standard mineral oily wastewater in a batch adsorption system. The effects of contact time and pH of solution on the emulsified oil uptake were investigated and discussed. It was found that the removal efficiency of emulsified oil increased with the increase in contact time. Biosorption was found to be less favorable at high acidic condition and a maximum removal was obtained at about neutrality. The isotherm study indicated that emulsified oil adsorption on SMBS was fitted well with the Langmuir model rather than the Freundlich model. The maximum adsorption capacity determined from the Langmuir isotherm was 518.6 mg g−1 at 25 °C. The kinetic study revealed that equilibrium time was achieved in less than 40 min and the kinetic data were fitted well to the pseudo-first-order model.